Exercise increases pancreatic β‐cell viability in a model of type 1 diabetes through IL‐6 signaling. Issue 5 (21st January 2015) - Paula, Flavia M. M.; Leite, Nayara C.; Vanzela, Emerielle C.; Kurauti, Mirian A.; Freitas‐Dias, Ricardo; Carneiro, Everardo M.; Boschero, Antonio C.; Zoppi, Claudio C.
ABSTRACT: Type 1 diabetes (T1D) is provoked by an autoimmune assault against pancreatic β cells. Exercise training enhances β‐cell mass in T1D. Here, we investigated how exercise signals β cells in T1D condition. For this, we used several approaches. Wild‐type and IL‐6 knockout (KO) C57BL/6 mice were exercised. Afterward, islets from control and trained mice were exposed to inflammatory cytokines (IL‐1β plus IFN‐γ). Islets from control mice and β‐cell lines (INS‐1E and MIN6) were incubated with serum from control or trained mice or medium obtained from 5‐aminoimidazole‐4 carboxamide 1‐β‐d ‐ribofuranoside (AICAR)‐treated C2C12 skeletal muscle cells. Subsequently, islets and β cells were exposed to IL‐1β plus IFN‐γ. Proteins were assessed by immunoblotting, apoptosis was determined by DNA‐binding dye propidium iodide fluorescence, and NO* was estimated by nitrite. Exercise reduced 25, 75, and 50% of the IL‐1β plus IFN‐γ‐induced iNOS, nitrite, and cleaved caspase‐3 content, respectively, in pancreatic islets. Serum from trained mice and medium from AICAR‐treated C2C12 cells reduced β‐cell death, induced by IL‐1β plus IFN‐γ treatment, in 15 and 38%, respectively. This effect was lost in samples treated with IL‐6 inhibitor or with serum from exercised IL‐6 KO mice. In conclusion, muscle contraction signals β‐cell survival in T1D through IL‐6.—Paula, F.M.M., Leite, N. C., Vanzela, E. C., Kurauti, M. A., Freitas‐Dias, R., Carneiro, E. M., Boschero, A. C., Zoppi, C. C. Exercise increases pancreatic β‐cell viability in a model of type 1 diabetes through IL‐6 signaling. FASEB J. 29, 1805‐1816 (2015). www.fasebj.org